Culturally-Based Copyright Systems?: The U.S. and Korea in Conflict - Ilhyung Lee (Washington University Law Quarterly, 2001)
This Article offers a more complete elaboration of the cultural dimension of copyright, principally for the Korean copyright system, but to some extent for the U.S. system as well. In so doing, this Article examines the cultural attitudes reflected in each jurisdiction’s copyright, and critiques and measures those cultural attitudes for practical and current applicability. This process ensures that the matter of culture in copyright receives the balanced attention that it is due. Awareness of the cultural aspects of each other’s copyright system will be important in future discussions between the United States and Korea, especially in light of the ongoing tension between the two over the piracy situation.
Keywords: Copyright -- United States; Copyright -- Korea (South); Product counterfeiting; Korea (South) -- Civilization; Comparative law; Intellectual property; Culture; Piracy (Copyright)